2010
DOI: 10.1155/2010/560495
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and 3D-CT Follow-Up of Extrahepatic Portal Vein Aneurysm: A Case Report

Abstract: Extrahepatic portal vein aneurysm is a rare disorder. From 1956 to 2008, we found only 43 published English-language reports, including 67 cases, using Pub Med. We report a case of a 77-year-old woman who had complaints of lower abdominal fullness and residual urine. We performed ultrasonography (US), which demonstrated a congenital extrahepatic portal vein aneurysm. She had no obvious symptoms of the extrahepatic portal vein aneurysm. She had undergone gastrectomy without blood transfusion for gastric ulcer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The congenital origin is supported by the presence of the aneurysms in children and young adults without portal hypertension and liver disorder [1][2][3][4][5][6][7]. A proposed pathogenesis of this congenital form is congenital weakness of the venous wall.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The congenital origin is supported by the presence of the aneurysms in children and young adults without portal hypertension and liver disorder [1][2][3][4][5][6][7]. A proposed pathogenesis of this congenital form is congenital weakness of the venous wall.…”
Section: Discussionmentioning
confidence: 99%
“…Normal portal vein diameters in children range from 3 mm to 11 mm [6]. In fact, Yukawa et al [1] reported that the size of EPVA ranged from 8 mm to 115 mm in 68 cases ages between 0 and 83 years. The size of EPVA on the first day of life was measured to be 1.5 cm on US [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations